TEORI-TEORI EKONOMI POLITIK INTERNASIONAL DALAM PERBINCANGAN: ALIRAN DAN PANDANGAN - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2015)
This article briefly describes some of the major theories of international political economy, namely: Liberal Trade Theory; Nationalist trade theory; The theory of